BUDGETARY CONTROL SYSTEM AS PREDICTORS OF FINANCIAL PERFORMANCE OF MANUFACTURING COMPANIES IN SOUTH-WEST, NIGERIA (NAU Journal of Technology and Vocational Education, 2025)
The study focused on budgetary control system as predictors of financial performance of manufacturing companies in South-West, Nigeria. Two null hypotheses were tested. Correlational survey research design was adopted for the study. The population comprised 44,082 budgetary control personnel in 18,666 manufacturing companies in South-West Nigeria. Proportionate stratified random sampling technique was used to select a sample size of 4409 budgetary control personnel. The instrument for data collection was a structured questionnaire. The instrument was validated by three experts. Cronbach Alpha method was used to obtained reliability co-efficient internal consistency and the values obtained were 0.91 and 0.90. Simple regression analysis was used to test the null hypotheses at 0.05 alpha level. The findings revealed that variance analysis budgetary control and responsibility accounting budgetary control significantly predict financial performance of manufacturing companies in South-West, Nigeria based on budgetary control personnel years of work experience. The study concluded that manufacturing companies’ failure to use variance analysis budgetary control and responsibility accounting budgetary control and financial budgetary control effectively could result to the company being financially unsuccessful and inability to invest to make profit.
Keywords: Budgetary Control System; Financial Performance; Manufacturing Companies